Pancarpal Arthrodesis in a Cat: A Case Report and Anatomical Study - Simpson, D.; Goldsmid, Sarah (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
A carpometacarpal hyperextension injury in a cat was treated by pancarpal arthrodesis, following the failure of conservative treatment. An 8-hole 1.5 mm mini plate was placed on the dorsal aspect of the distal radius, carpus and third metacarpal bone. An aluminium spoon splint was used for six weeks postoperatively, until radio-graphs revealed bone union. The body weights and the dimensions of the distal radius, radiocarpal bone and third metacarpal bone from the left limb of 15 cadavers were recorded in order to aid the selection of appropriate implants for future cases.Pancarpal arthrodesis was used to treat a cat with a carpometacarpal hyperextension injury. The use of an 8-hole 1.5 mm mini plate applied to the dorsal surface of the carpus, in combination with limb splinting provided effective stabilization. An excellent functional result was obtained. Measurements of the radius, radial carpal and third metacarpal bones from 15 cadavers suggest that 1.5 mm bone screws are the largest that should be used for carpal arthrodesis in the average sized cat.
Keywords: Pancarpal; hyperextension; arthrodesis; anatomy; cat